2018
DOI: 10.1016/j.otsr.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Coronal trunk imbalance in idiopathic scoliosis: Does gravity line localisation confirm the physical findings?

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…7) where a cone is described of the spine only with the apex of the cone at the sacrum, in distinction to the cone of economy described by Dubousset 6 with the apex at the feet. The MCID from the confidence ellipse for coronal offset from this work confirms the previously published amount of ± 20 mm [11][12][13] . The sagittal offset is larger than the values previously quoted the literature 10 who, using a technique of measurements from a plumb line dropped behind the subject, recorded the sagittal balance (a difference of horizontal distance from the plumb line between that measured at the C7 and S2 vertebral levels) as 19.3 ± 17 mm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…7) where a cone is described of the spine only with the apex of the cone at the sacrum, in distinction to the cone of economy described by Dubousset 6 with the apex at the feet. The MCID from the confidence ellipse for coronal offset from this work confirms the previously published amount of ± 20 mm [11][12][13] . The sagittal offset is larger than the values previously quoted the literature 10 who, using a technique of measurements from a plumb line dropped behind the subject, recorded the sagittal balance (a difference of horizontal distance from the plumb line between that measured at the C7 and S2 vertebral levels) as 19.3 ± 17 mm.…”
Section: Discussionsupporting
confidence: 90%
“…Assessments of the range of normality in the measures of coronal and sagittal offset have been reported in the literature using a number of different measurement techniques [9][10][11][12][13] . The literature suggests that a coronal offset of 0 mm ± 28 mm (mean ± 95% CI) and a sagittal offset of between 90 mm of negative offset (C7 vertebral body or vertebra prominens (VP) posterior to the sacrum) and 61 mm of positive offset (C7 or VP anterior to the sacrum) (± 95% CI) would be accepted as representing a non-pathologic state [9][10][11][12][13] . However, these values are one dimensional, being reported separately from each other.…”
mentioning
confidence: 99%
“…1), and patients who did not respect this position were excluded. This significantly limits the uncertainty of the gravity line position, as was confirmed by validation studies on healthy subjects and scoliotic patients, which reported an uncertainty of the GL position lower than 9 mm [10,14].…”
Section: Discussionmentioning
confidence: 78%
“…Patient's gravity line (GL), vertebral axial rotations (VAR), and intervertebral axial rotations (IAR) were computed from the 3D reconstruction. The estimation of GL from 3D reconstruction of body envelope was validated on healthy and scoliotic patients [10], by comparison to a Wii Board, with a mean difference of 0.8 kg (SD 1.2) for the mass estimation and 0.5 mm (SD 1.2) for COM location, respectively.…”
Section: D Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation